Erdosteine salvages cardiac necrosis: Novel effect through modulation of MAPK and Nrf‐2/HO‐1 pathway. Issue 12 (30th July 2020) - Mutneja, Ekta; Verma, Vipin K.; Malik, Salma; Sahu, Anil K.; Ray, Ruma; Bhatia, Jagriti; Arya, Dharamvir S.
Abstract: Isoproterenol (ISO) induced oxidative stress and inflammation is involved in the pathogenesis of myocardial necrosis. To optimize the effect of erdosteine against myocardial necrosis, male albino Wistar rats were divided into eight groups ( n  = 6), that is, normal, ISO‐control, erdosteine pretreatment with ISO. Rats were administered erdosteine orally for 28 days. Two doses of ISO (85 mg/kg), s.c. were given to ISO‐C and erdosteine treatment groups on the 27th and 28th day. On the 29th day, hemodynamic parameters were recorded and the heart was excised for further parameters. In ISO‐C rats, significantly increased levels of inflammatory markers, pro‐oxidants, and structural damage were observed as compared with normal group. Furthermore, immunohistochemistry and terminal deoxynucleotidyl transferase dUTP nick end labeling revealed an increased expression of apoptotic proteins. Erdosteine at 80 mg/kg reversed the deleterious effects of ISO and normalized myocardium. Erdosteine showed anti‐inflammatory, antiapoptotic, and antioxidant activities through inhibition of MAPK and Nrf‐2/HO‐1 pathways. To conclude, erdosteine was found protective in ISO‐induced myocardial necrosis through MAPK and Nrf‐2/HO‐1 pathway. Abstract :